Spatial Patterns of Crime in Israel: Investigating the Effects of Inter-urban Inequality and Proximity - Boris A Portnov (European Regional Science Association (ERSA), 2003)
Many crimes in Israel, specifically property-related, are perpetrated by those who live outside localities where the crime is committed. As a result, crime rates are strongly affected by settlement patterns: Affluent localities surrounded by poor towns tend to exhibit relatively high crime rates. In order to measure the effect of urban inequality and proximity on crime rates, the Index of Relative Income (IRI) is proposed. This index is estimated as the ratio between the average income in a town and that in its neighbouring localities. As multivariate analysis indicates, the proposed index helps to explain the variation of property crime rates across urban localities, implying that the spatial unevenness of urban development (i.e. aerial proximity of affluent and poor towns) may spur property crimes. The findings of the present study lend support to regional development programs, aimed at minimizing spatial disparities in regional and urban development.
Keywords: 330